Status gizi pada balita komunitas adat terpencil di suatu wilayah kecamatan di Jambi - Asparian Asparian; Willia Novita Eka Rini (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Determinants of nutrition in toddlers of Remote Indigenous Communities (KAT) in Batang Hari RegencyPriority program of RPJMN 2014-2019 are empowerment programs, basic needs, accessibility and social service for citizens of indigenous people. Basic needs are food, clothing, housing, health, education, employment, and/or social service. The health problems of KAT are helminthiasis disease, skin disease, ISPA, diarrhea and low nutritional status in the group of children. This research is quantitative research with observational design through Cross Sectional approach to measure all variables at the same time. The population of all infant ages 24 – 59 months at the location of KAT village Sungai Terap subdistrict Batin XXIV District Batang hari. amples are total populations with inclusion criteria and exclusion criteria. Independent variables are family head income (KK), food availability, consumption patterns and public nutritional services. While the dependent variable is the nutritional status (TB/U). Primary data is obtained through interviews and observations using questionnaires and check-lists, secondary data is derived from the study of documents and interviews. Analysis of Univariate, bivariate and multivariate data using Chi Square test. The results found a significant between the KK income with stunting ρ = 0,000 OR = 22.7 and consumption patterns with stunting ρ = 0,002. The consumption of family rice is still very small, averaging 500 grams/hr. Highest consumption rate occurs when getting big game results, once in three weeks. There is no link between food availability and nutritional services with stunting. Multivariate test found the most significant determinant of stunting in toddlers aged 24 – 59 months at KAT Sungai Terap is KK income with OR = 14,0 value, income obtained only from the rubber plantation area of 0.8 Ha/KK and animal sales Category.